Practical reasoning and transnational justice John Rawls's argumentation on justice in dialogue with Onora O'Neill's Kantian cosmopolitanism - McArdle, Jill (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2015)
This thesis evaluates two opposing accounts of justice and international justice that both claim Kantian foundations: firstly, the international account offered by the political philosopher John Rawls, and, secondly, the cosmopolitan account argued for by the moral philosopher Onora O’Neill. The primary focus of the research is the adequacy of their contrasting strategies of justification for principles of justice. The primary conclusion is that Rawls's justificatory strategy lacks the impartial perspective it claims and is fundamentally insufficient and unsuited to the actual global context with which modern liberal pluralist democracies find themselves. This conclusion is based on an analysis of Rawls's methodological starting points, which it is argued lead him away from universal-moral justification toward a context- dependent and partisan form of justification.
Keywords: Religions and Theology, Ph.D.; Ph.D. Trinity College Dublin